Avaliação ecotoxicológica de efluente hospitalar utilizando ensaios embrionários com Danio Rerio - Ottonelli, Catiusa Kuchak Rosin (2016)
The acute toxicity evaluation following the FET (Fish Embryo Toxicity) method presents as a proposal the utilization of fish embryos as a replacement of adults fishes. This method was originally developed and standardized in Germany with the objective of being an alternative for the toxicity evaluation of effluents using fishes in 48h experiments. In 2013, the OECD (Organisation for Economic Co-operation and Development) suggested 96h experiments for the toxicity evaluation of chemical substances. However, there is a lack of information referring to this method using effluent samples. Therefore, the objective of this study was to evaluate if the 96h FET method can be used as an alternative for the evaluation of hospital effluent samples. In order to assess the FET efficiency, results were compared with different methods: larval D. rerio (10 + 2 days, unstandardized method), juveniles D. rerio and larval P. promelas, following NBR ISO 15088, 2011. Two exposure periods (48 e 96h) were analyzed and the CL50 (48 and 96h) were calculated aiming to evaluate if the exposure period were sufficient to observe the sample toxicological. Intending to increase the FET sensibility, three new toxic effects were included in evaluation: no outbreak, edemas and larval immobility; these were considered as subletal FET. The experiments with different development phases of D. rerio showed that the OECD 236 did not present the highest sensibility over other methods. Larval phases (D. rerio – 10 + 2 days) and P. promelas presented the highest sensibilities, followed by Subletal FET. FET method did not present significant differences only when compared with tests using 2 + 1 cm juveniles, executed according to NBR ISO 15088, 2011. The results between FET 48h and 96h exposure did not present any significant differences. Nevertheless, despite that the effects provided by OECD were observed in the first 48 exposure hours, the tests extension to 96h allowed the observation of different effects, increasing the method sensibility. This study concluded that using OECD FET method with D. rerio embryos for the evaluation of hospital effluents toxicity was not the more sensible method when compared with otheres methods and it should be cautiously observed.